The Theory of High-Temperature Superconductivity in Many-band Systems. MgB2 - Palistrant, M.E.; Kon, L.Z. (Відділення фізики і астрономії НАН України, 2010)
The main stages of development of the theory of superconducting systems with overlapping energy bands are formulated. The main references of the classical papers of the author of this theory, Prof. V.A. Moskalenko, and his coworkers are listed. The list also includes papers related to high-temperature superconductivity. Some peculiarities of the two-band model which gives qualitatively new results in comparison with the usual one-band model, are enumerated. The application of the two-band model to the description of thermodynamical properties of compound MgB2 is also discussed. The references covering our research of the kinetic properties of superconductors with overlapping energy bands are provided. In particular, we present the Ginzburg–Landau (GL) equations for the two-band superconductors doped with impurities and the results on the influence of impurities on the energy gap, as well as those concerning the dynamical properties of twoband superconductors. Сформульовано основнi етапи розвитку теорiї надпровiдних систем iз зонами, що перекриваються. Наведено основнi посилання на класичнi роботи автора цiєї теорiї, професора В.Л. Москаленко, i його спiвробiтникiв разом iз роботами з високотемпературної надпровiдностi. Вiдзначено особливостi двозонної моделi, яка дає якiсно новi результати порiвняно зi звичайною однозонною. Обговорено застосування двозонної моделi для опису термодинамiчних властивостей сполуки MgB2. Дано огляд наших дослiджень кiнетики надпровiдникiв iз зонами, що перекриваються. Зокрема, наведено рiвняння Гiнзбурга–Ландау для двозонних надпровiдникiв з домiшками та результати впливу домiшок на ширину забороненої зони. Розглянуто динамiчнi властивостi двозонних надпровiдникiв.